Procalcitonin clearance for early prediction of survival in critically ill patients with severe sepsis - Mat Nor, Mohd Basri; Md Ralib, Azrina (Hindawi Publishing Corporation, 2014)
Introduction. Serum procalcitonin (PCT) diagnosed sepsis in critically ill patients; however, its prediction for survival is not well established. We evaluated the prognostic value of dynamic changes of PCT in sepsis patients. Methods. A prospective observational study was conducted in adult ICU. Patients with systemic inflammatory response syndrome (SIRS) were recruited. Daily PCT were measured for 3 days. 48-h PCT clearance (PCTc-48) was defined as percentage of baseline PCT minus 48-h PCT over baseline PCT. Results. 95 SIRS patients were enrolled (67 sepsis and 28 non-infectious SIRS). 40% patients in the sepsis group died in hospital. Day 1-PCT was associated with diagnosis of sepsis (AUC 0.65 (95% CI, 0.55 to 0.76)), but was not predictive of mortality. In sepsis patients, PCTc-48 was associated with prediction of survival (AUC 0.69 (95% CI, 0.53 to 0.84)). Patients with PCTc-48 > 30% were independently associated with survival (HR 2.90 (95% CI 1.22 to 6.90)). Conclusions. PCTc-48 is associated with prediction of survival in critically ill patients with sepsis. This could assist clinicians in risk stratification; however, the small sample size, and a single-centre study, may limit the generalisability of the finding. This would benefit from replication in future multi-centre study.